2020
DOI: 10.1111/lcrp.12171
|View full text |Cite
|
Sign up to set email alerts
|

When and how are lies told? And the role of culture and intentions in intelligence‐gathering interviews

Abstract: Purpose. Lie-tellers tend to tell embedded lies within interviews. In the context of intelligence-gathering interviews, human sources may disclose information about multiple events, some of which may be false. In two studies, we examined when lie-tellers from low-and high-context cultures start reporting false events in interviews and to what extent they provide a similar amount of detail for the false and truthful events. Study 1 focused on lie-tellers' intentions, and Study 2 focused on their actual response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In another paper, Deeb and colleagues (2020) evaluated the location of lies and truths in interviews across those from high-and low-context cultures. The results generally suggested that people told lies toward the end of an interview, presumably to prepare for their deception and gauge the responsiveness of the interviewer (Deeb et al, 2020). Those who lied at the beginning of an interview suggested that this strategy might have been unexpected by the interviewer or to simply "be done with the lie" (Deeb et al, 2020, p. 13).…”
Section: The Current Investigationmentioning
confidence: 99%
“…In another paper, Deeb and colleagues (2020) evaluated the location of lies and truths in interviews across those from high-and low-context cultures. The results generally suggested that people told lies toward the end of an interview, presumably to prepare for their deception and gauge the responsiveness of the interviewer (Deeb et al, 2020). Those who lied at the beginning of an interview suggested that this strategy might have been unexpected by the interviewer or to simply "be done with the lie" (Deeb et al, 2020, p. 13).…”
Section: The Current Investigationmentioning
confidence: 99%